Wind Chill - Jacobs, Gregory; Gangemi, Joseph; Katz, Steven; Broadbent, Graham; Czernin, Pete (Culver City, Calif.: Sony Pictures Home Entertainment, 2007)
Two college students driving home for Christmas are forced off a deserted road in a snow storm and haunted by the ghosts who died there
Title from title screen
Executive producers, George Clooney, Ben Cosgrove, Steven Soderbergh
Cast: Emily Blunt, Ashton Holmes, Martin Donovan
DVD Format
In English, Spanish, Portuguese or Thai with English, Spanish, Portuguese, or Chinese subtitles
Keywords: Ghosts -- Drama; College students -- Drama; Automobile driving in winter -- Drama